2021
DOI: 10.33448/rsd-v10i11.19761
|View full text |Cite
|
Sign up to set email alerts
|

Modelos de predição aplicados a cinética de secagem solar da goiaba

Abstract: A goiaba apresenta excelentes características nutricionais, sendo considerada uma importante matéria prima na indústria de alimentos. Para a utilização eficiente desse fruto, é necessária a adoção de técnicas de conservação que retardem as perdas de qualidade decorrentes do processo de amadurecimento. A secagem por meio de energia solar devido ao seu potencial e baixo custo, configura-se como uma alternativa economicamente viável para a conservação de produtos agroindustriais. Assim, objetivou-se com esse estu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Reis et al [9], when evaluating the water content of acerola pulps, identified an average value of 90.75 g/100 g, close to that identified in this work. Studying this same parameter in guava pulp, Maia et al [10] found a value of 85.60 g/100 g, while Lins et al [11] and Rivas et al [12] reported mean values of 83.5 and 89.78 g/100 g, respectively, also close to those shown in Table 1. Reis et al [13] found values of 90.06, 83.44 and 88.18 g/100 g in yellow, purple, and orange passion fruit pulp, respectively, levels close to those found in this work.…”
Section: Physicochemical Characterizationmentioning
confidence: 57%
“…Reis et al [9], when evaluating the water content of acerola pulps, identified an average value of 90.75 g/100 g, close to that identified in this work. Studying this same parameter in guava pulp, Maia et al [10] found a value of 85.60 g/100 g, while Lins et al [11] and Rivas et al [12] reported mean values of 83.5 and 89.78 g/100 g, respectively, also close to those shown in Table 1. Reis et al [13] found values of 90.06, 83.44 and 88.18 g/100 g in yellow, purple, and orange passion fruit pulp, respectively, levels close to those found in this work.…”
Section: Physicochemical Characterizationmentioning
confidence: 57%